Pengaruh Pengelolaan Kegiatan Main terhadap Interaksi Sosial Anak Usia 5-6 Tahun Di PAUD Cinta Bangsa - Narimah, Samaniati; Rachmayani, Ika; Jaelani, Abdul Kadir (Mataram University, 2025)
The objective of this study is to ascertain the impact of managing play activities on the social interaction skills of children aged 5-6 years at PAUD Cinta Bangsa, East Pemenang Village, Pemenang District, North Lombok Regency. The research method employed is a Quantitative Quasi-Experimental Design, specifically a